Interfacial delamination crack profile estimation in polymer foam-cored sandwich composites. (15th June 2019) - Mitra, Nilanjan; Patra, AlakKumar; Mondal, Shyamal; Datta, Prasanta Kumar
Highlights: Embedded fiber Bragg grating (FBG) sensor for real-time interfacial delamination. Interfacial crack profile estimation with wavelength division multiplexing of FBG. Non-parabolic crack profile estimation for polymer foam-cored sandwich composites. Abstract: Parabolic profile of cracks is well known in fracture mechanics, which typically develops in metallic systems. The profile of Interfacial delamination cracks in polymer foam cored sandwich composite structure is being investigated in this work using a procedure of embedded fiber Bragg grating sensor array with wavelength division multiplexing. The observed arbitrary nature of the crack profile in the mode I dominated loading condition, raises questions on the parabolic crack profile as well as on the assumption of numerous variables for numerical simulations of crack propagation problems especially for polymer foam-cored sandwich materials.